Pengaruh Temperatur Hot Gun dan Sudut Kampuh V pada Hot Gas Welding Terhadap Kekuatan Uji Tekuk Sambungan Las HDPE - Ahmad Fauzi; Elka Faizal (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The development of construction materials is currently very rapid, including in the manufacture of fishing boats that still use wood. As an alternative, High Density Polyethylene (HDPE) plastic can replace wood because of its various advantages. The process of making fishing boats uses the plastic welding method, where the material is heated close to the melting temperature with a welding gun. The welding rod melts due to heat and is pressed continuously while the welding gun moves backward. This study aims to determine the effect of variations in the hot gas welding process on mechanical tests, especially bending tests on plastic welding joints. The two independent variables used are the hot gun temperature (250°C, 300°C, and 350°C) and the V bevel angle (60°, 75°, and 90°). The five controlled variables include the anvil temperature of 150°C, 3,2 mm thick HDPE plastic sheet, hot gas speed welding method, 5 mm diameter HDPE plastic additives, 7 liters/minute air flow rate, 1.2 mm/s welding speed, and 2 mm root gap. The research results are expected to obtain the maximum value of the bending test strength from the interaction of hot gun temperature variations and V-beam angles, as well as being a reference in making fishing boat bodies from HDPE using the hot gas welding method.